Impact of p53 knockdown on protein dataset of HaCaT cells - Daniil D. Romashin; Alexander L. Rusanov; Peter M. Kozhin; Maxim N. Karagyaur; Olga V. Tikhonova; Victor G. Zgoda; Nataliya G. Luzgina (Data in Brief, 2022)
The HaCaT line of immortalized non-tumor cells is a popular model of keratinocytes used for dermatological studies, in the practice of toxicological tests, and in the study of skin allergic reactions. These cells maintain a stable keratinocyte phenotype, do not require specific growth factors during cultivation, and respond to keratinocyte differentiation stimuli. HaCaT cells bear two mutant p53 alleles - R282Q and H179Y. At least two mechanisms of GOF (gain-of-function) of mutant p53 are known: it affects functions of p63/p73 by inhibiting their binding to DNA; or it binds to new DNA sites by interacting with other transcription factors (NF-Y, E2F1, NF-KB, VDR, p63). Proteins of the P53 family play an important role in the regulation of proliferation and differentiation processes of human keratinocytes. Proteomic study of HaCaT cells with TP53 gene knockdown provides new data for understanding the limitations of HaCaT cells when using them as an experimental model of normal human keratinocytes.In this article we present datasets obtained through the high-throughput shotgun proteomics analysis of human immortalized HaCaT keratinocytes and p53 knockdown HaCaT keratinocytes. As a protocol for proteomic profiling of cells, we used the approach of obtaining LC-MS/MS measurements followed by their processing with MaxQuant software (version 1.6.3.4). The “RAW” files were deposited to the ProteomeXchange with identifier PXD033538.